Voluntary pension funds contribution in the pension system of Latvia in comparison with Estonia and Lithuania - Dundure, Evija; Sloka, Biruta (University of Latvia, 2020)
Pension system formation is one of the questions on the daily agenda for most countries of the world. Most attention and discussion focus on the first two pension system pillars – state compulsory unfunded pension scheme and the state-funded or accumulated pension scheme in pension funds, both based on mandatory contributions. Private voluntary investments are the “third pillar” of pension systems and the gear to ensure an adequate level of income at retirement age by creating private pension funds. Voluntary savings are becoming the source of retirement income received on a monthly basis in line with the progress of private pension funds and expansion of the choice of pension schemes. This research task is to evaluate the 3rd pension pillar's current results in Latvia and create a comparison with Lithuania and Estonia. The research outlines the common and the differences between engagement in financial future planning decisions of the population in Baltic States and existing legislative frameworks to promote the formation of private pension funds. It rises the research question on the importance of the role of voluntary savings in each country as well as gives recommendations for further voluntary savings advancement. Research methods used are the analysis of scientific publications, acts of legislation and previously conducted research, analysis of statistical data on the development of voluntary pension fund contributions in Latvia and comparison with Lithuania and Estonia.
Keywords: pension system; voluntary savings; pension funds; private pension; Research Subject Categories::SOCIAL SCIENCES::Business and economics